Synthesis of Fluorescence Turn‐On DNA Hybridization Probe Using the DEAtC 2′‐Deoxycytidine Analog. Issue 1 (18th October 2018) - Turner, M. Benjamin; Anderson, Brooke A.; Samaan, George N.; Coste, Michael; Burns, Dillon D.; Purse, Byron W.
Abstract: DEA tC is a tricyclic 2′‐deoxycytidine analog that can be incorporated into oligonucleotides by solid‐phase synthesis and that exhibits a large fluorescence enhancement when correctly base‐paired with a guanine base in a DNA‐DNA duplex. The synthesis of DEA tC begins with 5‐amino‐2‐methylbenzothiazole and provides the DEA tC nucleobase analog over five synthetic steps. This nucleobase analog is then silylated using N, O ‐bis(trimethylsilyl)acetamide and conjugated to Hoffer's chlorosugar to provide the protected DEA tC nucleoside in good yield. Following protective‐group removal and chromatographic isolation of the β‐anomer, dimethoxytritylation and phosphoramidite synthesis offer the monomer for solid‐phase DNA synthesis. Solid‐phase DNA synthesis conditions using extended coupling of the DEA tC amidite and a short deprotection time are employed to maximize efficiency. By following the protocols described in this unit, the DEA tC fluorescent probe can be synthesized and can be incorporated into any desired synthetic DNA oligonucleotide. © 2018 by John Wiley & Sons, Inc.